Kidney size in relation to ageing, gender, renal function, birthweight and chronic kidney disease risk factors in a general population. Issue 4 (29th August 2018) - Piras, Doloretta; Masala, Marco; Delitala, Alessandro; Urru, Silvana A M; Curreli, Nicolò; Balaci, Lenuta; Ferreli, Liana P; Loi, Francesco; Atzeni, Alice; Cabiddu, Gianfranca; Racugno, Walter; Ventura, Laura; et al.
Abstract: Background: The relationship of kidney size to ageing, kidney function and kidney disease risk factors is not fully understood. Methods: Ultrasound length and parenchymal kidney volume were determined from a population-based sample of 3972 Sardinians (age range 18–100 years). We then identified the subset of 2256 'healthy' subjects to define age- and sex-specific reference ranges (2.5–97.5 percentile) of kidney volume. Logistic regression (accounting for family clustering) was used to identify the clinical characteristics associated with abnormally large kidneys or abnormally small kidneys. Results: In the healthy subset, kidney volume and length increased up to the fourth to fifth decade of life followed by a progressive decrease in men, whereas there was a gradual kidney volume decrease throughout the lifespan of women. In the whole sample, independent predictors of lower kidney volume (<2.5 percentile for age and sex) were male sex, low body mass index, short height, low waist:hip ratio and high serum creatinine (SCr); the independent predictors of larger kidney volume (>97.5 percentile for age and sex) were younger age, female sex, diabetes, obesity, high height, high waist:hip ratio and lower SCr. Estimated heritability for kidney volume was 15%, and for length 27%; kidney volume correlated strongly with birthweight. Conclusions: Overall, in a general healthy population, kidney measures declined with age differently in men and women. The determinants of kidney parenchymal volume include genetic factors and modifiable clinical factors.